Simple Recoder (SRc): Alat Bantu Pengkodean Hasil Kuesioner Online - R. Pasifikus Christa Wijaya (Journal of Health and Behavioral Science, 2019)
Online survey is considered as an effective means to collect research data. The use of the internet benefits researchers to get large sample sizes in almost unlimited reach. Unfortunately, the editing and coding of the results of the current survey is often constrained by outcomes that are still in the form of word responses. We introduce Simple Recoder (SRc) to make it easier for researchers to provide codes on response responses, especially on the results of online surveys. This tool will make it easier for researchers and students to organize data from online survey results.